Multi-modal Mn–Zn ferrite nanocrystals for magnetically-induced cancer targeted hyperthermia: a comparison of passive and active targeting effects. Issue 38 (18th July 2016) - Xie, Jun; Yan, Caiyun; Yan, Yu; Chen, Ling; Song, Lina; Zang, Fengchao; An, Yanli; Teng, Gaojun; Gu, Ning; Zhang, Yu
Abstract : The high performance and increased tumor-targeting accumulation of magnetic nanocrystals (MNCs) are the most important considerations in cancer targeted magnetic hyperthermia (TMH). Abstract : The high performance and increased tumor-targeting accumulation of magnetic nanocrystals (MNCs) are the most important considerations in cancer targeted magnetic hyperthermia (TMH). To achieve these goals, our study was firstly done using well-established fluorescence/magnetic Mn–Zn ferrite MNCs (core size: 14 nm) as multi-modal imaging contrast agents and highly-efficient "heat generators", which were coated with a biocompatible PEG-phospholipid (DSPE-PEG2000) and further modified by a cyclic tripeptide of arginine-glycine-aspartic acid (RGD). By using a mouse model bearing breast carcinoma (4T1), we then systematically compared PEGylated MNCs (MNCs@PEG)- and RGD-PEGylated MNCs (MNCs@RGD)-mediated tumor targeting abilities by intravenous administration. The MNCs@PEG-based passive targeting could successfully accumulate at the tumor due to the enhanced permeability and retention (EPR) effects, but the non-targeted localization might make the MNCs@PEG "leaking" from larger pores of tumor fenestrated vascular networks. Our designed MNCs@RGD, simultaneously functionalized with PEG and RGD ligands, might promote a synergistic effect including efficient tumor vasculature active targeting and EPR-mediated passive targeting, improving total MNC concentration and retention time in tumor tissues. By combining fluorescence/magnetic resonance (MR)/thermal multi-modal imaging-guided diagnostics and continuous TMH treatment under an alternating current magnetic field (ACMF, 2.58 kA m −1, 390 kHz), the tumor surface could be heated to approximately 43–44 °C based on the MNC-mediated repeated injections. Sufficient temperature elevation induced the apoptosis of tumor cells, and inhibited the tumor angiogenesis. Compared with MNCs@PEG, the active MNCs@RGD-based tumor targeting MR image was significantly more efficient due to both the higher and long-lasting tumor accumulation, but its antitumor efficacy was not obviously improved in the TMH treatments. To achieve a singularly promising tumor TMH therapy, a greatly increased MNC content in tumor was needed. This insight indicated that not only the tumor vasculature targeting, but also the active tumor cells targeting of MNCs should receive considerable attention in future clinical TMH therapy application.